2011
DOI: 10.1530/eje-11-0289
|View full text |Cite
|
Sign up to set email alerts
|

Long-term DHEA substitution in female adrenocortical failure, body composition, muscle function, and bone metabolism: a randomized trial

Abstract: Context: Adrenal derived androgens are low in women with adrenal failure. The physiological consequences of substitution therapy are uncertain. Objective: To investigate the effects of DHEA substitution in women with adrenal failure on body composition, fuel metabolism, and inflammatory markers. Design, participants and intervention: In this study, ten female patients (median age 38.5 years, range 28-52) with adrenal failure were treated with DHEA 50 mg for 6 months in a double-blind, randomized, placebo-contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 34 publications
0
10
0
1
Order By: Relevance
“…In vivo, lower androgen levels may contribute to sexual dimorphism of circulating adipokine levels, which was also demonstrated in our healthy and affected cohorts [ 39 , 54 , 55 , 61 ]. These results add up to the current discussion concerning metabolic benefits of the DHEA replacement in adrenal failure, which remain controversial despite several randomized trials [ 53 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 62%
“…In vivo, lower androgen levels may contribute to sexual dimorphism of circulating adipokine levels, which was also demonstrated in our healthy and affected cohorts [ 39 , 54 , 55 , 61 ]. These results add up to the current discussion concerning metabolic benefits of the DHEA replacement in adrenal failure, which remain controversial despite several randomized trials [ 53 , 62 , 63 ].…”
Section: Discussionmentioning
confidence: 62%
“…Six-month DHEAS treatment in women with adrenal insufficiency did not affect MCP-1 levels despite increased LBM [27], but fat distribution was unchanged and MIF data were not available in the study. Interestingly, animal studies showed that rats express MIF in Leydig cells, but whether MIF affects human reproduction is undetermined [25, 28].…”
Section: Discussionmentioning
confidence: 99%
“…We deleted 1930 duplicates, then 3283 articles were eliminated according to the title and abstract of the trials. In the next stage, 217 trials based on the full text were surveyed and lastly 14 articles with 10 arms on cortisol, [22][23][24][25][26][27][28][29][30] 5 articles with 6 arms on adiponectin, 9,27,28,31,32 2 articles with 3 arms on leptin, 9,31 2 articles with 3 arms on AST 9,32 and 4 articles with 5 arms on ALT 12,[32][33][34] (Figure 1). Table 1 lists the characteristics of 14 included articles.…”
Section: Study Selection and Characteristics Of The Eligible Trialsmentioning
confidence: 99%